Improvement of cargo consolidation in the export logistics process of a zinc refinery: the Nexa Resources Cajamarquilla case study - García Moncada, Enrique Antonio (2019)
This research aims to contribute to find a new alternative for the cargo consolidation process at Nexa Resources Cajamarquilla. This process implies the transportation of final products to the external warehouse by wagons, containers filling activities and the transportation of filled containers to port terminals. Qualitative data were collected during semi-structured interviews with managers and professionals from different fields with a high level of experience and background, since a process improvement involves knowing the impact in terms of manufacturing, sales, finance, corporate management and supply chain activities within the company. In terms of content analysis, time and cost, management of shipments and benefits of a new alternative were defined as the three main categories since APM Terminals can provide Nexa Resources with not only the possibility to reduce logistics costs and transportation time, but also the improvement of management of shipment process of the firm. The findings of this research suggest that choosing a new strategy for cargo consolidation process, using LICSA and APM Terminals at the same time will provide the firm with the opportunity to have a significant impact on saving costs and process efficiency; taking into consideration the decision of avoiding a dependence on an exclusive warehouse.